Correlation Between Learning Environment at School and Mathematics Learning Outcomes for the Fourth Grade Student of Elementary Schools in Kebumen Sub-District in Academic Year of 2019/2020 - Atmaja, Purwaka; Joharman, Joharman; Hidayah, Ratna (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
Abstract. Correlation Between Learning Environment at School and Â Mathematics Learning Outcomes for the Fourth Grade Student of Elementary Schools in Kebumen Sub-District in Academic Year of 2019/2020. The research aims to examine positive correlation between learning environment at school and mathematics learning outcomes and to determine the contribution learning environment at school toward mathematics learning outcomes for the fourth grade students of elementary schools in Kebumen sub-district in academic year of 2019/2020. The research is a quantitative research with correlation method. The samples are obtained by cluster random sampling with Statistical Product and Serice Solution (SPSS) application. The samples are 349 students in twelve elementary schools in Kebumen Sub-District. The data collection techniques include questionnaire and test. Data analysis uses pearson product-moment correlation test with significance level 0.05 and adjusted R square. The correlation test finds sig = 0,000 (sig < 0,05). It means that there is positive and significant correlation between learning environment at school and mathematics learning outcomes. It shows the better learning environment at school, the higher mathematics learning outcomes. Learning environment at school contributes mathematic learning outcomes by 13,1% and the remaining 86.9% is influenced by other factors. The results of this study are in accordance with existing theories and are also supported by relevant research.Keywords: learning environment at school, mathematics learning outcomes